2015
DOI: 10.1016/j.aqpro.2015.02.088
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Groundwater Quality for Drinking Purpose in Rural Areas Surrounding a Defunct Copper Mine

Abstract: The suitability of groundwater quality of 22 wells located in the rural areas surrounding Ingaldhal defunct copper mine in Chithradurga district of Karnataka state was assessed for drinking purpose based on the various water quality parameters. Standard methods for physicochemical analysis of groundwater samples were employed. The results of analysis carried out showed the following concentration ranges: pH (7.61-8.34), EC (950-3120μS/cm), TH (410-1400mg/l), TDS (594-1913mg/l), F -(0.15-1.43mg/l), NO 3 -(14-16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(41 citation statements)
references
References 8 publications
3
35
0
3
Order By: Relevance
“…Even though the limits of chloride have been mostly reduced to the physical approach (taste), there have been no adverse health effects on humans who are exposed to high dose of Cl − [20]. Similarly, about 80% of all the samples had fluoride values that are within the acceptable guideline for potable water and this observable pattern was in agreement with previous studies reported [8] [12]. It was further reported in the same study that the relatively low levels of fluoride in ground water might be due to its acidic nature which renders it immobile.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Even though the limits of chloride have been mostly reduced to the physical approach (taste), there have been no adverse health effects on humans who are exposed to high dose of Cl − [20]. Similarly, about 80% of all the samples had fluoride values that are within the acceptable guideline for potable water and this observable pattern was in agreement with previous studies reported [8] [12]. It was further reported in the same study that the relatively low levels of fluoride in ground water might be due to its acidic nature which renders it immobile.…”
Section: Resultssupporting
confidence: 90%
“…4 SO − ) is presumed to be dominant across the sites and a similar observation was reported in a recent study [12] where strong acids predominate over weaker acids. The strong acidity of well waters around the sites is in contrast to a previous study conducted in Guinea where the pH content was skewed to be alkaline [13].…”
Section: Resultssupporting
confidence: 82%
“…Groundwater is a priceless resource of drinking water that is used for domestic utilization, industrial activities, as well as agriculture. It is commonly of good quality as compared to other water resources due to filtration in soil [1,2]. However, locative differences of groundwater quality are dependent on geological structure through which it flows and human activities near the groundwater basin [3].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the study site is covered entirely by sedimentary lithounits enriched in sandstone and limestone (CGWB 2007); (Herman 1978); (Basavarajappa and Manjunatha 2015). It reaches the groundwater by ion exchange processes (Annapoorna and Janardhana 2015). Magnesium is commonly found in ferromagnesian minerals in igneous rocks and as carbonates in sedimentary rocks.…”
Section: Calcium and Magnesium (Ca 21 And Mg 21 )mentioning
confidence: 99%